2 answers:
Answer:
x^4 - x^2 - 2x - 1
Step-by-step explanation:
(x^2+x+1)(x^2-x-1) = x^4 - x^3 - x^2 + x^3 - x^2 - x + x^2 - x - 1
= x^4 - x^2 - 2x - 1
Answer:
option 4
Step-by-step explanation:
(f*g)(x) =(x² + x+ 1)*(x² - x -1)
= x²*(x² - x -1) + x(x² - x -1) + 1*( x² - x -1)
= x²*x² - x²*x -x²*1 + x*x² - x*x -x*1 + x² - x -1
= x⁴ - x³ - x² +x³ - x² - x + x² - x -1
= x⁴ - x³ + x³ - x² - x² + x² - x - x - 1
= x⁴ - x² - 2x - 1
You might be interested in
the difference between those two bird wingspans is 115.4 inches
Answer:
b or a
Step-by-step explanation:
Answer:
c
Step-by-step explanation:
your right
3
the ans is 3 ---
4
cause blue is 5 times of red.
I believe it should be 5.3487 since 283% is converted into 2.83 and multiplied by 1.89.